Structural self-organization of C60 and cisplatin in physiological solution. Issue 39 (21st October 2015) - Prylutskyy, Yu. I.; Cherepanov, V. V.; Evstigneev, M. P.; Kyzyma, O. A.; Petrenko, V. I.; Styopkin, V. I.; Bulavin, L. A.; Davidenko, N. A.; Wyrzykowski, D.; Woziwodzka, A.; Piosik, J.; Kaźmierkiewicz, R.; et al.
<x xml:space="preserve">Abstract</x> The specific features of structural self-organization of C60 fullerene and antitumor drug cisplatin (Cis) in physiological solution (0.9% NaCl) have been investigated.